Complex Surface Chemistry of an Otherwise Inert Solvent Molecule: Tetrahydrofuran on Si(001). Issue 17 (22nd September 2014) - Mette, Gerson; Reutzel, Marcel; Bartholomäus, Ruben; Laref, Slimane; Tonner, Ralf; Dürr, Michael; Koert, Ulrich; Höfer, Ulrich
Abstract The reaction of tetrahydrofuran (THF), an otherwise inert solvent molecule, on Si(001) was experimentally studied in ultra‐high vacuum. Using scanning tunneling microscopy (STM) and photoelectron spectroscopy at variable temperature, we could both isolate a datively bound intermediate state of THF on Si(001), as well as the final configuration that bridges two dimer rows of the Si(001) surface after ether cleavage. The latter configuration implies splitting of the OC bond, which is typically kinetically suppressed. THF thus exhibits a hitherto unknown reactivity on Si(001).